FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN MAKANAN PENDAMPING ASI (MP-ASI) DINI PADA BAYI DI PUSKESMAS - Nina Mirania, Ayu; Lexy Louis, Stephanie (Jurnal Kesmas Prima Indonesia, 2024)
Nutritional problems are a part that greatly influences the growth and development of babies and more than 50% of deaths of children under five are related to malnutrition, among these deaths are related to inappropriate feeding practices. The aim of this research is to determine the factors associated with early provision of complementary breast milk (MP-ASI) to babies. This type of research uses an analytical survey with a cross sectional approach. The population is all mothers who have babies aged 6-24 months in the 11 Ilir Community Health Center Area, Palembang City. Sampling used accidental sampling technique, totaling 63 respondents. The analysis technique uses the chi square statistical test. The research results showed that 30.2% of respondents provided early MP-ASI, 57.1% of respondents who had low education, 95.2% of respondents who did not work and 58.7% of respondents who were multiparous. The results of statistical tests show that there is a relationship between maternal education (p value 0.022 with an OR result of 0.243), and parity (p value 0.020 with an OR result of 3.673) with giving early MP-ASI to babies but there is no relationship with maternal employment (p value 0.902) . Advice from health workers is to always provide health education in order to increase mothers' knowledge regarding the proper provision of MP-ASI.